The modern face of right-wing populism in Brazil - L. S. Okuneva (Ибероамериканские тетради, 2022)
The right-wing populist phenomenon has become one of the main trends in world politics. Its spread in the “old” and “new democracies” forces researchers to reconsider the categorical apparatus by means of which they analyzed world processes in the very recent past. Characteristic features, manifesting themselves in different countries, inevitably acquire a local flavor. The surge of right-wing populism in Europe was provoked by an external factor – migration flows, but in Brazil there were purely internal reasons and motives that created fertile ground for the right-wing populist leader to come to power, while in the USA it was a mixture and interweaving of both internal and external factors. The author analyzes the Brazilian version of modern right-wing populist ideology and political practice, embodied in the “Bolsonaro phenomenon”. The author examines reasons and circumstances that made possible the emergence and implanting of right-wing populism on Brazilian political terrain. The paper indicates main features of right-wing populism in its “Bolsonarist” version. It is shown that the Brazilian right-wing populism of the beginning of the 21st century reflects both the modern world trend and all the classic signs of populism, and at the same time has its own unique national characteristics. The “Bolsonaro phenomenon” brings forward many debatable problems.